2015
DOI: 10.1007/s13197-014-1701-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green tea powder on thermal, rheological & functional properties of wheat flour and physical, nutraceutical & sensory analysis of cookies

Abstract: Green tea powder (GTP) was incorporated in wheat flour at different levels (1, 2 and 4 %) and its effect on quality parameters of flour and cookies were studied. Thermal analysis showed that addition of GTP did not increase the onset temperature, end temperature and enthalpy of flour significantly. However, the increase in GTP content retarded the retro gradation of the gelatinized wheat flour gel and decreased the water absorption capacity, Oil absorption capacity, water solubility index, Foam capacity and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
45
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 35 publications
12
45
1
2
Order By: Relevance
“…Hydrolysis experiments were carried out in a 1500 L reaction vessel maintained at 50°C with the solution being agitated by an over-head stirrer. The hydrolysis process was adequately controlled by monitoring the degree of hydrolysis (DH) using the pH-stat technique (Adler-Nissen 1986). Aliquots (250 ml) were taken at 5, 10, 15 and 20 % DH.…”
Section: Enzymatic Modification Of Milk Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrolysis experiments were carried out in a 1500 L reaction vessel maintained at 50°C with the solution being agitated by an over-head stirrer. The hydrolysis process was adequately controlled by monitoring the degree of hydrolysis (DH) using the pH-stat technique (Adler-Nissen 1986). Aliquots (250 ml) were taken at 5, 10, 15 and 20 % DH.…”
Section: Enzymatic Modification Of Milk Proteinsmentioning
confidence: 99%
“…The hydrolysis was carried out using the pH-stat method described by Adler-Nissen (1986) and the DH (%) was calculated from the volume and the molarity of alkali used to maintain constant pH.…”
Section: Calculation Of the Degree Of Hydrolysis (Dh)mentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants offer numerous health benefits such as anticancerous, antidiabetic and antihypertensive effects (Ahmad et al , 2015Gani et al 2016;Rahmanian et al 2015). pH of pineapple juice ranges between 3 to 4, which is lower than the isoelectric point of β-lactoglobin and lower pH increases energy barrier for unfolding of the proteins, which hinders the non-covalent (disulphide interactions) bonding (Hoffmann and van Mil 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Jongberg et al (2013) showed that green tea extract reduces oxidation of lipids and the level of formation of carbonyls in bologna-type sausage made with pork meat, prepared under oxidative stress; however, the loss of thiol and protein crosslink (indicators of proteins oxidation) did not diminish. Ahmad et al (2015) added green tea extract at different levels (1, 2 and 4%) to wheat flour to make cookies. Sensory analysis revealed that the addition of 4% green tea extract to wheat flour increased the acceptability of color, aroma and taste.…”
Section: Green Teamentioning
confidence: 99%